Curcumin: a potential anti-photoaging agent - Nie, Yuhong; Li, Yiming (Frontiers in Pharmacology, 2025)
Turmeric, also referred to as Curcuma longa, is a commonly used spice, recognized for its demonstrated effects in reducing inflammation, combating microbes, providing antioxidant benefits, slowing the aging process, and exhibiting anticancer potential. The process of skin aging is intricate, with ultraviolet radiation being a significant extrinsic factor. Increasing evidence suggests that curcumin, the active component of turmeric, can prevent ultraviolet radiation-induced skin photoaging and related inflammation. Its effects include inhibition of melanin production, wrinkle reduction, antioxidant and anti-inflammatory actions. This review primarily focuses on the specific signaling pathways involved in skin photoaging and the mechanisms by which curcumin mitigates photoaging. Key topics include the antioxidant and anti-inflammatory properties of curcumin, regulation of matrix metalloproteinase, regulation of autophagy and apoptosis, improvement of pigmentation, and regulation of microbial balance. Additionally, addressing the critical issue of curcumin’s low bioavailability, the review summarizes the latest advancements in curcumin formulation improvements. This article aims to provide a comprehensive overview of curcumin’s progress of skin photoaging research and offer evidence for its further clinical application in dermatological treatments. The review contributes to a deeper understanding of the potential molecular mechanisms of curcumin in combating photoaging and presents new insights for the development of curcumin-based anti-photoaging products.